Multiagency approaches to preventing sudden unexpected death in infancy (SUDI): a review and analysis of UK policies - Michelle Baldwin; Dorothy Newbury-Birch; Fiona Roberts; Helen L Ball; Anne Holt; Alice-Amber Keegan; Daniel R Whitehouse; Louise S Cooper; Sophie R Lovell-Kennedy; Laura M Murray; Nicola J Cleghorn; Amanda Healy; et al. (BMJ Publishing Group, 2023)
Background Recent reviews of sudden unexpected deaths in infancy (SUDI) in England recommend a multiagency working (MAW) approach to prevention but lack clear guidance around how this might be implemented.Aims In England, local authorities commission and oversee public health services. This review examines how local authority policies address implementation of MAW for SUDI prevention to understand local variations and identify strengths and weaknesses.Methods Using a comprehensive list of all metropolitan, county, unitary councils and London boroughs in England, we systematically searched local authority websites for relevant published documents and submitted freedom of information (FOI) requests where policies or guidance for SUDI prevention had not been sourced online. We extracted data from documents using a standardised form to summarise policy contents which were then collated, described and appraised.Findings We searched the websites of 152 council and London boroughs, identifying 36 relevant policies and guidelines for staff. We submitted 116 FOI requests which yielded 64 responses including six valid documents: 45% (52/116) of local authorities did not respond. Seventeen councils shared the same guidance under safeguarding partnerships; removal of duplicates resulted in 26 unique documents. Only 15% (4/26) of the documents included a detailed plan for how MAW approaches were to be implemented despite 73% (19/26) of the documents mentioning the importance of engaging the MAW in raising awareness of safe sleep for babies with vulnerable families. Five areas of variation were identified across policies: (1) scope, (2) responsibilities, (3) training, (4) implementation and (5) evaluation.Conclusions There are discrepancies between local authorities in England in whether and how MAW for SUDI prevention is carried out. Strengths and weaknesses of approaches are identified to inform future development of MAW for SUDI prevention.